Odpowiedzi

2010-04-14T15:15:30+02:00
C) 5x+13=23
5x=10
x=2
d) 3x+11=41
3x=30
x=10
e) -x+2=8
-x=6
x=-6
f) -x+5=-2
-x=-7
x=7
g) -2x-7=11
-2x=18
x=-9
h) -5x+3=-12
-5x=-15
x=3
2010-04-14T15:17:38+02:00
5x+13=23
5x=23-13
5x=10/5
x=2

3x+11=41

3x=41-11
3x=30/3
x=10

-x+2=8
-x=8-2
-x=6*(-1)
x=-6


-x+5=-2
-x=-2-5
-x=-7*(-1)
x=7

-2x-7=11
-2x=11+7
-2x=18/(-2)
x=-9


-5x+3=-12
-5x=-12-3
-5x=-15/(-5)
x=3

2010-04-14T15:20:15+02:00
5x+13=23
5x=23-13
5x=10 / : 5
x=2 w kazdym przykladzie przenosisz zwykla liczbe (bez x)na druga strone zmieniając znak

3x+11=41
3x=41-11
3x=30 /: 3
x=10

-x+2=8
-x=8-2
-x=6 / * -1
x=-6

-x+5=-2
-x=-2-5
-x=-7/*-1
x=7

-2x-7=11
-2x=11+7
-2x=18 / ; -2
x=-9

-5x+3=-12
-5x=-12-3
-5x=-15/:-5
x=3
PozdrOO ;*